Child-Like Adults: Dual-Task Effects on Collective vs. Distributive Sentence Interpretations - de Koster, Anna M. B.; Hendriks, Petra; Spenader, Jennifer K. (Frontiers in Psychology, 2021)
In this work we consider a recent proposal that claims that the preferred interpretation of sentences containing definite plural expressions such as “The boys are building a snowman” is not determined by semantic composition, but is pragmatically derived via an implicature. Plural expressions can express that each member of a group acts individually (distributive interpretation) or that the group acts together (collective interpretation). While adults prefer collective interpretations for sentences that are not explicitly marked for distributivity by the distributive marker each, children do not show this preference. One explanation is that the adult collective preference for definite plurals arises due to a conversational implicature. If implicature calculation requires memory resources, children may fail to calculate the implicature due to memory limitations. This study investigated whether loading Dutch-speaking adults’ working memory using a dual task would elicit more child-like distributive interpretations, as would be predicted by the implicature account. We found that loading WM in adults did lead to response patterns more similar to children. We discuss whether our results offer a plausible explanation for children’s development of an understanding of distributivity, and how our results relate to recent debates on the role of cognitive resources in implicature calculation.